Peripheral nerve injury results in a biased loss of sensory neuron subpopulations - Cooper, AH; Barry, AM; Chrysostomidou, P; Lolignier, R; Wang, J; Redondo Canales, M; Titterton, HF; Bennett, DL; Weir, GA (Lippincott, Williams & Wilkins, 2024)
There is a rich literature describing the loss of dorsal root ganglion (DRG) neurons following peripheral axotomy, but the vulnerability of discrete subpopulations has not yet been characterised. Furthermore, the extent or even presence of neuron loss following injury has recently been challenged. In this study, we have used a range of transgenic recombinase driver mouse lines to genetically label molecularly defined subpopulations of DRG neurons and track their survival following traumatic nerve injury. We find that spared nerve injury leads to a marked loss of cells containing DRG volume and a concomitant loss of small-diameter DRG neurons. Neuron loss occurs unequally across subpopulations and is particularly prevalent in nonpeptidergic nociceptors, marked by expression of Mrgprd. We show that this subpopulation is almost entirely lost following spared nerve injury and severely depleted (by roughly 50%) following sciatic nerve crush. Finally, we used an in vitro model of DRG neuron survival to demonstrate that nonpeptidergic nociceptor loss is likely dependent on the absence of neurotrophic support. Together, these results profile the extent to which DRG neuron subpopulations can survive axotomy, with implications for our understanding of nerve injury-induced plasticity and pain.